Transfusion of HIV‐infected blood products despite highly sensitive nucleic acid testing. Issue 6 (19th February 2019) - Cappy, Pierre; Barlet, Valérie; Lucas, Quentin; Tinard, Xavier; Pillonel, Josiane; Gross, Sylvie; Tiberghien, Pierre; Laperche, Syria
Abstract : BACKGROUND: In France, the risk of HIV transmission by transfusion was reduced by implementing pooled nucleic acid testing (NAT) in 2001 and individual NAT in 2010. We report here the first case in France of transfusion of human immunodeficiency virus (HIV)‐infected blood donated during HIV pre–ramp‐up phase that tested individual NAT negative. METHODS: Blood donations are screened for HIV antibodies and HIV RNA (ProcleixUltrio, Grifols; limit of detection at 95%, 23 copies/mL). When a repeat donor tests positive for HIV, a repository sample from the previous donation is tested with the Cobas Taqman HIV‐1 test (CTM, Roche; limit of detection at 95%, 17 copies/mL). RESULTS: In August 2017, a 57‐year‐old male repeat donor was screened positive for HIV antibodies and RNA (plasma viral load, 11, 599 copies/mL). The previous donation had tested negative with Ultrio in March 2017 but was positive with an unquantifiable plasma viral load when tested with CTM. Sequencing showed no mismatch between Ultrio primers/probes and the target sequence. HIV transmission was excluded by lookback studies in the recipient of platelets, which had been pathogen reduced, but not in the recipient of RBCs due to premature death. CONCLUSION: This case demonstrates that the risk of contaminated donations due to the early HIV infection phase going undetected by highly sensitive NAT is real but exceptional. The absence of transmission to the platelets recipient could be due to the very low viral inoculum and/or to the efficacy of the viral inactivation. This case also highlights the additional value of a systematic donation archiving and the importance of donor education and predonation selection.